Observer-based Robust Control for Dynamic Positioning of Large-Scale Heavy Lift Vessels. Issue 3 (2019) - Ye, Jun; Roy, Spandan; Godjevac, Milinko; Baldi, Simone
Abstract: With the growing demand of large-scale heavy lift vessels in the deep-sea offshore construction works, high performance of Dynamic positioning (DP) systems is becoming ever crucial. However, current DP systems on board of heavy lift vessels do not consider model uncertainty (typically arising from mooring forces). In this paper, an observer-based robust controller is designed that can tackle model uncertainty in hydrodynamic damping and mooring forces, environmental disturbances as well as can filter out the high-frequency vessel movement. Closed-loop system stability is analytically established in terms of uniformly ultimately boundedness. In addition, several key performance indicators are provided for tuning the performance of the controller. The effectiveness of the proposed control framework is studied in simulation with a crane-vessel system.